Evaluation of marine psychrophile, Psychrobacter namhaensis SO89, as a probiotic in Nile tilapia (Oreochromis niloticus) diets. Issue 61 (February 2017) - Makled, Sarah O.; Hamdan, Amira M.; El-Sayed, Abdel-Fattah M.; Hafez, Elsayed E.
Abstract: Marine environment represents a promising source of new, unconventional bioactive compounds with health-promoting abilities, which can be used as food supplements. The present study was carried out to evaluate the efficacy of marine Psychrobacter namhaensis SO89 on growth performance and immune response of Nile tilapia ( Oreochromis niloticus ). P. namhaensis were isolated from marine environments and phylogenetically identified by 16S rRNA gene sequences. The bacterial isolate was incorporated in Nile tilapia diets (30% crude protein) at three concentrations (0.0, 0.5 and 1.0%; w/w) (designated as T0, T0.5 and T1, respectively), which were equivalent to 0.0, 2.8 × 10 7 and 5.6 × 10 7 CFU g −1 diet, respectively. The diets were fed to Nile tilapia fingerlings (4.58 ± 0.14 g average weight) at a daily rate of 3% of their live body weights (BW), 3 times a day for 50 days. The best growth rates and feed utilization efficiency were obtained at 0.5% P. namhaensis SO89 concentration. Hematocrit (Ht%), hemoglobin (Hb%), erythrocytes (RBC) and total leukocyte (WBCs) values were significantly higher in P. namhaensis SO89- fed groups than in the control group. Similarly, immunoglobulin M (IgM), alternative complement hemolysis (ACH50), phagocytic and lysozyme activities significantly increased following dietary P. namhaensis SO89 supplementation at 0.5% concentration compared to the control group. The expression of IL-4 and IL-12 genes was also significantly up-regulated in P. namhaensis SO89-treated groups up to 0.5% concentration. Increasing bacterial concentration to 1% resulted in a significant decrease in fish performance and immune response. The present results suggest that marine psychrotolerant ( Psychrobacter namhaensis ) can be considered as a novel feed additive in Nile tilapia feeds. Highlights: We studied the effect of marine Psychrobacter namhaensis on growth performance and immune response of Nile tilapia. Fish were fed test diets supplemented with three concentrations of bacterial isolate (0.0, 0.5 and 1.0%). Supplemental P. namhaensis improved growth rates, feed utilization efficiency and immune response. The best performance was obtained at 0.5% bacterial concentration.